Understand your accounts a guide to small business finance - Price, Aubrey St. John (Kogan page, 1999)
The 4th revised edition gives simple and practical, but detailed guidance to the non-accountant on how to deal with everyday financial matters. Topics covered include: Making sense of a profit and loss account and balance sheets, Managing cash flow, Pricing of time and product, Stock control, Using budgets to plan for profits and much more.